Pengaruh Senam Kaki Diabetik Terhadap Kadar Glukosa Darah pada Penderita Diabetes Mellitus Tipe II - Asniati; Ulfa Hasana (STIKes Payung Negeri Pekanbaru, 2021)
Background: Diabetes Mellitus is one of the non-communicable diseases that will increase in number in the future. DM management non-pharmacological therapy is physical exercise which is one of the four main pillars of diabetes mellitus management, one of which is diabetic foot exercise. Objective: This study was to determine the effect of diabetic foot exercise on blood glucose levels in patients with type II diabetes mellitus in the working area of the Umbrella Health Center, Sekaki, Pekanbaru. Methods: This research is quantitative. Research Design: The design used is pre experimental designs with the design of ''One Group Pretest and Posttest. Sampling technique: Accidental sampling, namely all patients with Diabetes Mellitus encountered during the study. For simple experimental research, the number of sample members is 10 to 20 people. The sample in this study is 11 people. The results of this study concluded that there was a significant effect of diabetic foot exercise on blood glucose levels, the value of value = 0.000 < (0.05). This study recommends especially for people to be able to recognize diabetic foot exercises on changes in blood glucose levels.